Decitabine versus hydroxyurea for advanced proliferative chronic myelomonocytic leukemia: results of a randomized phase III trial within the EMSCO Network - Itzykson, Raphael; Santini, Valeria; Thepot, Sylvain; Ades, Lionel; Chaffaut, Cendrine; Giagounidis, Aristoteles; Morabito, Margot; Droin, Nathalie; Lübbert, Michael; Sapena, Rosa; Nimubona, Stanislas; Goasguen, Jean; et al. (Journal of clinical oncology, 2023)
PURPOSE - - Hydroxyurea (HY) is a reference treatment of advanced myeloproliferative neoplasms. We conducted a randomized phase III trial comparing decitabine (DAC) and HY in advanced myeloproliferative chronic myelomonocytic leukemias (CMML). - - PATIENTS AND METHODS - - Newly diagnosed myeloproliferative CMML patients with advanced disease were randomly assigned 1:1 to intravenous DAC (20 mg/m2/d days 1-5) or HY (1-4 g/d) in 28-day cycles. The primary end point was event-free survival (EFS), events being death and acute myelomonocytic leukemia (AML) transformation or progression. - - RESULTS - - One-hundred seventy patients received DAC (n = 84) or HY (n = 86). Median age was 72 and 74 years, and median WBC count 32.5 × 109/L and 31.2 × 109/L in the DAC and HY arms, respectively. Thirty-three percent of DAC and 31% of HY patients had CMML-2. Patients received a median of five DAC and six HY cycles. With a median follow-up of 17.5 months, median EFS was 12.1 months in the DAC arm and 10.3 months in the HY arm (hazard ratio [HR], 0.83; 95% CI, 0.59 to 1.16; P = .27). There was no significant interaction between treatment effect and blast or platelet count, anemia, CMML Prognostic Scoring System, Groupe Francophone des Myelodysplasies, or CMML Prognostic Scoring System-mol risk. Fifty-three (63%) DAC patients achieved a response compared with 30 (35%) HY patients (P = .0004). Median duration of response was similar in both arms (DAC, 16.3 months; HY, 17.4 months; P = .90). Median overall survival was 18.4 months in the DAC arm and 21.9 months in the HY arm (P = .67). Compared with HY, DAC significantly reduced the risk of CMML progression or transformation to acute myelomonocytic leukemia (cause-specific HR, 0.62; 95% CI, 0.41 to 0.94; P = .005) at the expense of death without progression or transformation (cause-specific HR, 1.55; 95% CI, 0.82 to 2.9; P = .04). - - CONCLUSION - - Compared with HY, frontline treatment with DAC did not improve EFS in patients with advanced myeloproliferative CMML (ClinicalTrials.gov identifier: NCT02214407).
Online veröffentlicht: 01. Dezember 2022
Gesehen am 28.07.2023